Long-Term Memory Function Impairments following Sucrose Exposure in Juvenile versus Adult Rats - Coirini, Hector (2022)
We previously described that excessive consumption of sucrose during youth produces fear memory and anxiety-like behavior in adulthood. Here, we evaluated whether high cognitive function is also affected by studying early sucrose consumption in object recognition memory (NOR). Male Sprague Dawley rats were tested for short-term, long-term, and consolidated NOR after 25 days of unlimited sucrose access in juvenile (PD 25–50) or adult age (PD 75–100). All rats spent equal time exploring the two objects during the sample phase T1. When animals were exposed for 2, 24 h or 7 days later to a copy of the objects presented in T1 and a novel object, the sucrose-exposed juvenile group failed to distinguish between the familiar and the novel objects in contrast with the rest of the groups. Sucrose-exposed animals developed hypertriglyceridemia and glucose intolerance, but juvenile animals showed increased fasting glycemia and sustained the glucose intolerance longer. Moreover, sucrose decreased hippocampal proBDNF expression in juveniles while it was increased in adults, and sucrose also increased RAGE expression in adults. The NOR exploration ratio correlated negatively with basal glycemia and positively with proBDNF. Taken together, these data suggest that sucrose-induced alterations in glucose metabolism may contribute to a long-term decline in proBDNF and impaired recognition memory.